Castration methods do not affect weight gain and have diverse impacts on the welfare of water buffalo males - Martins, L. T.; Gonçalves, M. C.; Tavares, K. C.S.; Gaudêncio, S.; Santos Neto, P. C.; Dias, A. L.G.; Gava, A.; Saito, M. E.; Oliveira, C. A.; Mezzalira, A.; Vieira, A. D. (Elsevier, 2011)
Castration is used to improve the management of water buffalo beef males raised under extensive conditions. However, as buffalo are considered robust animals, their welfare is often neglected, which, among other implications, may compromise their productivity. The aim of this study was to determine the effects of different castration methods on the stress level and weight gain of water buffalo males. Two experiments were performed with three treatments each. In experiment 1, serum cortisol concentrations were used as stress indicators for non-castrated (control group) or castrated males, either surgically or by burdizzo clamp. In experiment 2, blood levels of fibrinogen were used as stress indicators for males in the control group compared to those castrated by either burdizzo clamp or intratesticular injection of calcium chloride (chemical castration). In both experiments, clinical parameters and the mean daily weight gain were measured for all males. Surgical castration and chemical castration caused higher stress than castration with burdizzo, with no differences observed in weight gain among castration methods. In conclusion, for water buffalo males, castration with burdizzo clamp is preferable to surgical and chemical methods because it causes the lowest stress level in the animals. © 2011 Elsevier B.V.
Keywords: Bubalus bubalis; Burdizzo; Chemical castration; Cortisol; Fibrinogen; Orchiectomy